Association between surgical tracheostomy and chronic tracheal stenosis: A retrospective, single-center study - Kuwabara, Yuki; Yamakawa, Kentaro; Okui, Seiko; Miyazaki, Erica; Uezono, Shoichi (Frontiers in Medicine, 2022)
Background Tracheal stenosis is a major complication of tracheostomy. Accordingly, anesthesiologists tend to select a smaller endotracheal tube (ETT) than usual for patients with a prior tracheostomy history, regardless of the presence or absence of respiratory symptoms. However, it likely comes from our trial and error, not scientific evidence. Therefore, in this study, we retrospectively examined the association between traditional surgical tracheostomy and tracheal stenosis as assessed by transverse computed tomography (CT). Methods Patients who underwent surgery for head and neck cancer from January 2010 to December 2013, with a temporary tracheostomy closed within a couple of months, were included. Exclusion criteria were tracheostoma before surgery, permanent tracheostomy, or insufficient CT follow-up. Transverse CT slices were measured 2 cm above and below the tracheostomy site (0.5 cm/slice for a total of 9 slices). The minimum cross-sectional tracheal area and horizontal and vertical diameters in transverse CT slices were compared before (baseline: BL), 6 months (6M) and 12 months (12M) after tracheostomy. Tracheal stenosis was defined as a decrease in the minimum cross-sectional tracheal area compared to BL. Results Of 112 patients, 77 were included. The minimum tracheal area was significantly decreased at 6M and 12M compared to BL (BL: mean 285 [SD 68] mm2, 6M: 267 [70] mm2, P < 0.01 vs. BL, 12M: 269 [68] mm2, P < 0.01 vs. BL), and the localization was predominantly at or above the tracheostomy site at 6M and 12M. Tracheal stenosis was identified in 55 patients at 6M and in 49 patients at 12M without any respiratory symptoms. With regard to horizontal and vertical diameter, only horizontal diameter was significantly decreased at 6M and 12M compared to BL (BL: 16.8 [2.4] mm, 6M: 15.4 [2.7] mm, P < 0.01 vs. BL, 12M: 15.6 [2.8] mm, P < 0.01 vs. BL). Conclusion Conventional surgical tracheostomy was associated with a decreased horizontal diameter of the trachea. It resulted in a decreased cross-sectional tracheal area in more than one-half of the patients; however, no patient complained of any respiratory symptoms. Therefore, even without respiratory symptoms, prior tracheostomy causes an increased risk of tracheal stenosis, and using a smaller ETT than usual could be reasonable.